2020
DOI: 10.3389/fphar.2020.00574
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and In Vitro Studies of an Reactive Oxygen Species (ROS)-Responsive Methoxy Polyethylene Glycol-Thioketal-Melphalan Prodrug for Glioblastoma Treatment

Abstract: Glioblastoma (GBM) is the most frequent and aggressive primary tumor of the brain and averages a life expectancy in diagnosed patients of only 15 months. Hence, more effective therapies against this malignancy are urgently needed. Several diseases, including cancer, are featured by high levels of reactive oxygen species (ROS), which are possible GBM hallmarks to target or benefit from. Therefore, the covalent linkage of drugs to ROS-responsive molecules can be exploited aiming for a selective drug release with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 73 publications
(96 reference statements)
0
18
0
Order By: Relevance
“…Numerous basic and clinical studies have found that the level of lipid reactive oxygen species in tumor cells is higher than that of normal cells [26,27].Recently, ferroptosis, which involves lipid reactive oxygen species, has been proposed to be a potential therapeutic target for cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous basic and clinical studies have found that the level of lipid reactive oxygen species in tumor cells is higher than that of normal cells [26,27].Recently, ferroptosis, which involves lipid reactive oxygen species, has been proposed to be a potential therapeutic target for cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these problems, the idea of enzyme encapsulation into tailored nanoparticles (NPs) represents one of the most attractive strategies. Among current advances in developed NPs, polymer-based NPs have gained increasing attention as biocompatible, biodegradable, targeted, and versatile platforms [14][15][16][17][18][19][20] for the delivery of a wide array of therapeutic molecules ranging from small molecules [21][22][23][24], peptides [25][26][27][28], proteins and enzymes [2,4,[29][30][31], and genetic material [32][33][34]. The encapsulation of enzymes into polymeric NPs offer several advantages compared to conventional enzyme-based therapy, including: (i) stabilizing and protecting the enzyme; (ii) improving biological activity; (iii) possibility of targeted delivery; (iv) controlling the enzyme release kinetics; (v) improving therapeutic efficacy and safety [10,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Prodrugs are inactive precursors of a drug designed to increase the amount of drug converted to its active form by a certain pathological or biological stimulus [40][41][42]. With the prodrug idea in mind, ROS-sensitive TK linkers have been exploited to conjugate a drug to another drug or polymer that can then self-assemble into NPs [43]. Once the prodrug NPs reach the diseased tissues, the high concentration of ROS cleaves the TK linker to release and activate the drug (Figure 2b).…”
Section: Tk As Linkage To Form Prodrug or Polyprodrugsmentioning
confidence: 99%